2019
DOI: 10.3390/ijerph17010197
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Self-Isolate When Facing a Pandemic Risk: Model, Empirical Test, and Policy Recommendations

Abstract: Infected people are isolated to minimize the spread of pandemic diseases. Therefore, the factors related to self-isolation (SI) should not be neglected, and it is important to investigate the factors leading the infected (or possibly infected) people to choose to self-isolate. In this paper, we tried to show that the theory of planned behavior provides a useful conceptual framework for SI when facing a pandemic risk, and a regression method with Chinese provincial (Guangdong Province) data was applied to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
107
5
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(131 citation statements)
references
References 55 publications
13
107
5
6
Order By: Relevance
“…In addition, the present study found minor differences in demographic characteristics such as gender, age, and area of residence. In contrast to previous studies [58]; [50], we found no differences between males and females in how behavioral change is in uenced. These ndings are inconsistent with past studies that found differences in behavioral intention between the sexes [59].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In addition, the present study found minor differences in demographic characteristics such as gender, age, and area of residence. In contrast to previous studies [58]; [50], we found no differences between males and females in how behavioral change is in uenced. These ndings are inconsistent with past studies that found differences in behavioral intention between the sexes [59].…”
Section: Discussioncontrasting
confidence: 99%
“…The contribution of the PBC variable to the model indicates that people have control and the ability to take social distancing intention. This nding supports past TPB studies that have found PBC variables are typically less important than attitudes and social norms [50]; [51]; [52]; [52]; [53]. Contrary to our expectations, attitude was not predictor of intention.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, it is important to enforce physical (but not social) distancing measures in the COVID-19 crisis. Physical isolation measures are useful for blocking the spread of the virus and reducing the possibility of citizens being affected [ 51 ]. Measures such as these may increase the sense of security of the public.…”
Section: Discussionmentioning
confidence: 99%
“…Social psychology plays an important role in epidemic governance. From the social psychology perspective, the direct causation of behavior is the primary function of emotion [ 37 , 38 ], people in a strong state of psychological stress will make a variety of irrational behavior, and even coupled with the impact of events to cause secondary disasters. The present study built a conceptual model based on the SOR model, in which lockdown interacted with pandemic severity to predict psychological distancing, and thereby result in social anxiety.…”
Section: Discussionmentioning
confidence: 99%